Kakek sebagai figur pengganti ayah dalam novel Kembara Rindu karya Habiburrahman El Shirazy: Analisis berdasarkan teori Cinta Erich Fromm - Kurnia Candra Dewi; Agus Nuryatin (Universitas Ahmad Dahlan, 2026)
Studies examining substitute father figures in literary works through Erich Fromm’s theory of love remain limited, particularly those focusing on the role of grandfathers as primary caregivers and their relevance to strengthening character education in Indonesian language learning at the senior high school level. This study aims to describe the forms of grandfatherly love as a substitute father figure in the novel Kembara Rindu by Habiburrahman El Shirazy based on Erich Fromm’s theory of love and its relevance to strengthening character education in Indonesian language learning at senior high schools. This research employed a descriptive qualitative approach using literary psychology analysis. The primary data source was the novel Kembara Rindu by Habiburrahman El Shirazy, while the data consisted of dialogues, narrations, and events indicating forms of affection shown by the grandfather figure. Data were collected through reading and note-taking techniques and analyzed using Erich Fromm’s theory of love, which includes care, responsibility, respect, and knowledge. The results show that Grandfather Jirun demonstrates strong affection as a substitute father figure through caregiving, protection, emotional support, educational guidance, and the cultivation of moral values for his grandchildren, Udo Ridho and Syifa. The most dominant aspect of affection identified in this study is responsibility, reflected in Grandfather Jirun’s commitment to fulfilling the educational, emotional, and social needs of his grandchildren. In addition, the novel contains character education values, including religiosity, responsibility, hard work, social care, and respect for education, making it relevant as teaching material for Indonesian language learning, particularly in novel appreciation classes at the senior high school level.